2017
DOI: 10.3390/molecules22060944
|View full text |Cite
|
Sign up to set email alerts
|

Fruits of Black Chokeberry Aronia melanocarpa in the Prevention of Chronic Diseases

Abstract: In recent years, growing attention has been focused on the utilization of natural sources of antioxidants in the prevention of chronic diseases. Black chokeberry (Aronia melanocarpa) represents a lesser known fruit species utilized mainly as juices, purees, jams, jellies and wine, as important food colorants or nutritional supplements. The fruit is valued as a great source of antioxidants, especially polyphenols, such as phenolic acids (neochlorogenic and chlorogenic acids) and flavonoids (anthocyanins, proant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
221
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(240 citation statements)
references
References 122 publications
(215 reference statements)
8
221
0
11
Order By: Relevance
“…Therefore, minor phytochemicals were not quantified for the purpose of this study. The presence and the high content of bioactive polyphenolic phytochemicals, including anthocyanins, provide numerous health benefits, which have been reported for A. melanocarpa fruits and their preparations (Jurikova et al, 2017).…”
Section: Characterization Of Bcpementioning
confidence: 99%
“…Therefore, minor phytochemicals were not quantified for the purpose of this study. The presence and the high content of bioactive polyphenolic phytochemicals, including anthocyanins, provide numerous health benefits, which have been reported for A. melanocarpa fruits and their preparations (Jurikova et al, 2017).…”
Section: Characterization Of Bcpementioning
confidence: 99%
“…are known from their beneficial impact on human health (Boncheva et al, ; Borowska & Brzóska, ; Yamane et al, ). Consumption of these products is recommended as a prophylactic for various diseases, including non‐communicable diseases such as diabetes, obesity, digestive system disorders, cardiovascular system disorders and cancer (Boncheva et al, ; Borowska & Brzóska, ; Jurikova et al, ; Yamane et al, ). The study by Boncheva et al () has revealed that consumption of juice from chokeberries (200 mL daily for 60 days) improved liver function (estimated based on the serum activities of liver marker enzymes), carbohydrate metabolism and lipid parameters in the serum of people with NAFLD.…”
Section: Polyphenol‐rich Products In Protection and Treatment Of Cd‐imentioning
confidence: 99%
“…Various bioactive effects of Aronia melanocarpa (black chokeberry) for improving human's health (Banjari et al, 2017;Jurikova et al, 2017;Sic Zlabur et al, 2017). Nanu et al, 2007;Zeinhom and Abdel-Latef, 2014;El-Baz et al, 2017).…”
Section: Figmentioning
confidence: 99%
“…Recently, the usability of natural extracts has dramatically increased for improving human's health (Jakobek et al, 2007;Jurikova et al, 2017). Especially, among various natural compounds, Aronia has received important attention in recent years due to their various positive effects for human's health (Kokotkiewicz et al, 2010;Park and Hong, 2014;Banjari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation